The word is murder eaudiobook A novel. - Horowitz, Anthony (Hawthorne and Horowitz, 2018)
Narrated by Rory Kinnear ""One of the most entertaining mysteries of the year. It's also one of the most stimulating, as it ponders such questions as: Which is of greater interest to the reader, the crime or the detective? And: Is the pencil truly mightier than the butcher knife?" — Wall Street Journal New York Times bestselling author of Magpie Murders and Moriarty, Anthony Horowitz has yet again brilliantly reinvented the classic crime novel, this time writing a fictional version of himself as the Watson to a modern-day Holmes. A woman crosses a London street. It is just after 11 a.m. on a bright spring morning, and she is going into a funeral parlor to plan her own service. Six hours later the woman is dead, strangled with a crimson curtain cord in her own home. Enter disgraced police detective Daniel Hawthorne, a brilliant, eccentric man as quick with an insult as he is to crack a case. And Hawthorne has a partner, the celebrated novelist Anthony Horowitz, curious about the case and looking for new material. As brusque, impatient, and annoying as Hawthorne can be, Horowitz—a seasoned hand when it comes to crime stories—suspects the detective may be on to something, and is irresistibly drawn into the mystery. But as the case unfolds, Horowitz realizes that he's at the center of a story he can't control, and his brilliant partner may be hiding dark and mysterious secrets of his own.